Analisis Faktor-faktor yang Mempengaruhi Kepuasan Kerja Karyawan Penyandang Disabilitas - Ikromi, Ziyadi Ali; Hidayat, Novi; Rismawati, Rismawati (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Job satisfaction is a crucial factor in achieving optimal work results. Employees who feel satisfied with their work will naturally strive to the best of their ability to complete their work tasks, thereby achieving job performance. This study aims to identify various factors contributing to job satisfaction among employees with disabilities. The methodology used in this study is a Systematic Literature Review with a qualitative approach (meta-synthesis). Literature searches were conducted through various electronic databases, such as Researchgate, Scopus, Springer, Academia, and Google Scholar, using the keywords "job satisfaction of employees with disabilities" and "job satisfaction of employees with disabilities." The results of this literature study indicate that factors influencing job satisfaction among employees with disabilities are social support, work environment, work flexibility, psychological capital, and demographic factors.